2019
DOI: 10.1159/000495758
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoachalasia as First Manifestation of a Malignancy

Abstract: Pseudoachalasia is a condition in which symptoms, radiologic, endoscopic, and manometric findings mimick idiopathic achalasia. About 4% of patients with a typical constellation for idiopathic achalasia will turn out to have pseudoachalasia, posing a major diagnostic challenge. A large spectrum of underlying causes of pseudoachalasia has been described. However, in about 70% of affected patients, this condition is caused by a malignancy (mostly adenocarcinoma of the esophagogastric junction or cardia). We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In view of all of the above, I do not think that this patient's presentation speaks for the diagnosis of achalasia. In rare cases, achalasia may be mimicked by cancer (pseudoachalasia), which we have recently described in a very young patient [44]. However, the long history of dysphagia without symptom progression speaks against this diagnosis.…”
Section: Differential Diagnosismentioning
confidence: 97%
“…In view of all of the above, I do not think that this patient's presentation speaks for the diagnosis of achalasia. In rare cases, achalasia may be mimicked by cancer (pseudoachalasia), which we have recently described in a very young patient [44]. However, the long history of dysphagia without symptom progression speaks against this diagnosis.…”
Section: Differential Diagnosismentioning
confidence: 97%
“…This is the main mechanism by which adenocarcinoma of the gastroesophageal junction leads to pseudoachalasia. Fabian et al [82] reported pseudoachalasia as the first manifestation of a cardia adenocarcinoma in a patient that presented typical signs of achalasia at endoscopy, manometry, and the barium swallow test.…”
Section: Cancer Leading To Esophageal Dysmotilitymentioning
confidence: 99%
“…Most of the patients with neuronal paraneoplastic pseudoachalasia express serum autoantibodies, and the most common is the antineuronal nuclear antibody type-1 (ANNA-1; or Anti-Hu) [85]. Anti-acetylcholine and anti-neural calcium channel antibodies may be present in some patients as well [82,86]. Previous in vitro studies showed that these antibodies bind to neuronal antigens.…”
Section: Cancer Leading To Esophageal Dysmotilitymentioning
confidence: 99%
“…Malignancy is rarely associated with esophageal motility disorders, but when it occurs, it is more commonly linked to achalasia and associated primarily with adenocarcinoma of the cardia. 49,50 Cancer has also been occasionally reported in association with distal esophageal spasm (DES). 51 Recently, JE was added to the list of motility disorders that are associated with malignancy and systemic diseases.…”
Section: Neoplasia and Systemic Diseasesmentioning
confidence: 99%